A Quantitative Approach to Challenges Facing Online and Physical Classrooms in Higher Institution - Babalola, Ebenezer Omolafe; Oludare, Precious Ize (Bumi Publikasi Nusantara, 2024)
This study investigated the challenges facing online and physical classrooms in higher institutions. Descriptive research of the survey type was employed to achieve the purpose of this study. Students from five randomly selected faculties at the University of Ilorin, Nigeria made up the study target population. To choose the sample from each of the selected faculties, a proportionate sampling procedure was used. The actual sample size for the study was 200 Undergraduates, who were chosen using random selection techniques. Descriptive statistics of the mean score were used to analyze the information obtained from the respondents. The findings of this study show that students faced challenges while learning in both online and physical classrooms. It was concluded that despite the underlying similarities between online and physical classrooms, the two modalities are very different from one another. Online teaching is typically student-centered which necessitates active learning, in contrast to traditional classroom instruction, which has been known to be teachers-centered and calls for passive learning. It was a challenge for teachers to move from face-to-face in-class mode to virtual learning, changing their teaching methodologies, and managing their time. It was also a challenge to develop content that not only covers the curriculum but also engages the learners.